Affective Filters as Predictors of English Language Proficiency - John Francis Cruz (Journal of English as A Foreign Language Teaching and Research, 2025)
This study investigated the predictive role of affective filters in second language acquisition on English language proficiency among 285 Grade 9 learners at Biñan Integrated National High School, Philippines, during the third quarter of the academic year 2024-2025. The sample was determined using stratified sampling with proportional allocation. The study employed a quantitative approach, analyzing the descriptive levels of affective filters and English proficiency using mean scores and the correlation among these variables using multiple regression analysis. English language proficiency was assessed through a standardized test.  The results revealed a significant positive correlation between motivation and various aspects of English proficiency, highlighting its crucial role in language learning success. Conversely, anxiety demonstrated a significant negative correlation, indicating that higher anxiety levels are associated with lower proficiency. Self-efficacy showed a positive relationship with specific skills, particularly correct usage and grammar, suggesting its importance in targeted skill development.  Regression analysis further confirmed the significant predictive power of motivation and anxiety on overall English language proficiency. Based on these findings, the study concludes that motivation and anxiety are key determinants of English language proficiency, while self-efficacy plays a more nuanced role.  This study recommends that educational interventions prioritize fostering motivation through engaging and relevant learning experiences, alleviating anxiety by cultivating a supportive and non-threatening classroom environment, and enhancing self-efficacy through targeted instruction and opportunities for success.  Further research is suggested to explore other potential factors influencing English language proficiency